(3CaVd Yeds ((3GdbGgQIs (3hKjbIs, 2006)
(3GdYed CSGS GdMjGI,jQHj aj GdEfSGf Gdbje,jNOe ZjQg,jSGYO GdCNQjf(B..(3hdcf gd gfGc Yed CaVd ef GdCNQ,SDGd eMjQ,CKGQ acQ YeQ YfOeG WQMJ GdeYdeI SDGdgG (B..(3GTJQcJ GdCe GdhGYjIaj Md GdSDGds
(3GdbUI(B--s (3GdfTjO(B--s (3dYHI GdMQha GdCHLOjI(B--s (3dYHI GdCTjGA(B--s (3dYHI GdJdhjfs
(3ef (B4 (3Edj (B9 (3SfhGJs
2
Keywords: (3GdYeds -- (3GdCaVds -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs